Letter (copy) : Basque Children's Committee - Tewson, Vincent
1940-04-09 038-0043-001 Secretary's. HVT/FC/EK/877. 9th April, 1940. PERSONAL. Miss Eleanor Rathbone, M.P., National Joint Comittee for Spanish Relief, 50, Romney Street, Westminster, London, S.W.1. Dear Miss Rathbone, BASQUE CHILDREN'S COMMITTEE. Many thanks for your letter of the 8th instant enclosing a communication from the Duchess of Atholl. I am forwarding for your personal information a copy of a letter which I sent to the Duchess in reply to a request from her that we should consider giving further financial assistance. Will you please return this copy as soon as you have perused it? I am glad that your own feeling is in the direction of my own views. With the news this morning of the extension of the War I feel convinced that the Committee will have greater difficulty than ever in carrying on their work. I would be opposed to sending any children back to Spain if they could not rejoin at least one parent, but our own financial difficulties, coupled with the increasing physical danger to which these children will be exposed, convinces me that a child who entered this country at the age of 13 or 14 and who can rejoin one parent in Spain should be repatriated. P.T.O. 292/946/38/43(I)